2019
DOI: 10.1017/wet.2018.117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rate and timing of indaziflam on ‘Sunbelt’ and muscadine grape

Abstract: Studies were conducted at six locations across North Carolina to determine tolerance of ‘Sunbelt’ grape (bunch grape) and muscadine grape (‘Carlos’, ‘Triumph’, ‘Summit’) to indaziflam herbicide. Treatments included indaziflam (0, 50, 73 g ai ha–1) or flumioxazin (213 g ai ha–1) applied alone in April, and sequential applications of indaziflam (36, 50, 73 g ai ha–1) or flumioxazin (213 g ai ha–1) applied in April followed by the same rate applied in June. No crop injury was observed across locations. Muscadine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
(23 reference statements)
1
12
0
Order By: Relevance
“…Blueberry and blackberry production regions in the southeastern U.S. typically have acidic soils (pH 3.6 to 5.5) and use overhead or drip irrigation, therefore reducing potential indaziflam mobility. This was also noted by Basinger et al (2019), who noted no crop injury on grape and muscadine varieties up to and exceeding labeled rates in single and sequential applications. It was also noted that yield and yield components (berries per cluster, berry weight, cluster number per meter cordon) were not different than weed-free controls.…”
Section: Blackberrysupporting
confidence: 61%
See 3 more Smart Citations
“…Blueberry and blackberry production regions in the southeastern U.S. typically have acidic soils (pH 3.6 to 5.5) and use overhead or drip irrigation, therefore reducing potential indaziflam mobility. This was also noted by Basinger et al (2019), who noted no crop injury on grape and muscadine varieties up to and exceeding labeled rates in single and sequential applications. It was also noted that yield and yield components (berries per cluster, berry weight, cluster number per meter cordon) were not different than weed-free controls.…”
Section: Blackberrysupporting
confidence: 61%
“…Blackberry primocanes and floricanes exhibited no visual injury to any herbicide treatment (data not shown). As previously noted, there are many reports of little to no visual injury for indaziflam applied to perennial crops (Basinger et al 2019;González-Delgado et al 2017;Grey et al 2018Grey et al , 2016Hurdle et al 2019).…”
Section: Blackberrymentioning
confidence: 87%
See 2 more Smart Citations
“…Applied in the soil, the same herbicide led to stress reduction in leaf carbohydrates, a decrease in free amino acids, which could affect the vine vitality for a long-term (Saladin et al, 2003). On the other hand, a study of the effect of indaziflam and flumioxazin on the varieties Sunbelt, Carlos, Triumph, Summit found that the quality of grapes (extract, titratable acidity and pH) was not affected by the application of these herbicides (Basinger et al, 2019).…”
Section: Introductionmentioning
confidence: 99%